WebSphere version 5 application development handbook - Wahli, Ueli (IBM redbooks., 2003)
This IBM Redbooks publication provides detailed information on how to develop J2EE-compliant Web applications for WebSphere Application Server Version 5 using WebSphere Studio Application Developer Version 5.1 as an integrated development environment. Also covered are a variety of application development tools from IBM and Open Source. The target audience for this book includes the entire application development team, especially architects and developers. It also includes developers with experience of earlier versions of the WebSphere products, who are looking to migrate to Version 5. This book is organized in four main parts: - Introduction--covering the J2EE programming model, the development process, and software configuration management - Requirements, analysis, architecture, and design--covering the early phases of a project, using Rational XDE - Implementation--covering the coding of business logic, presentation, and Web services, using Application Developer - Debugging, unit testing, deployment, and measurements--covering the test and production phases of a project, using Application Developer, Application Server, and Open Source tools Throughout the book, we refer to PiggyBank, a sample J2EE application we create step-by-step to illustrate the use of the tools, concepts, and principles of the application development process. Please note that the additional material referenced in the text is not available from IBM.